Cigarette Smoke–induced Oxidative/Nitrosative Stress Impairs VEGF- and Fluid Shear Stress–Mediated Signaling in Endothelial Cells - Edirisinghe, Indika (Mary Ann Liebert, Inc., 2010)
VEGF receptor 2 (VEGFR2), a tyrosine kinase receptor, is activated by VEGF and fluid shear stress (FSS), and its downstream signaling is important in the regulation of endothelial functions, such as cell migration, endothelium-dependent relaxation, and angiogenesis. Cigarette smoke (CS) is known to cause oxidative/nitrosative stress, leading to modifications of tyrosine kinase receptors and impaired downstream signaling. We hypothesized that CS-induced oxidative/nitrosative stress impairs VEGF- and FSS-mediated VEGFR2 activation, leading to endothelial dysfunction. Human lung microvascular endothelial cells and human umbilical vein endothelial cells were treated with different concentrations of cigarette smoke extract (CSE) to investigate the VEGF- or FSS-mediated VEGFR2 phosphorylation and its downstream signaling involved in endothelial function. CSE treatment impaired both VEGF- and FSS-mediated VEGFR2 phosphorylation, resulting in impaired endothelial nitric oxide synthase (eNOS) phosphorylation by Akt. CS-derived reactive oxygen/nitrogen species react with VEGFR2, rendering VEGFR2 inactive for its downstream signaling. Pretreatment with nitric oxide scavenger (PTIO), reactive oxygen species scavengers (combination of SOD with catalase), and N-acetyl-l-cysteine, significantly attenuated the CSE-induced impairment of VEGF-mediated Akt and eNOS phosphorylation. These findings suggest that CSE-induced oxidative/nitrosative stress impairs VEGF- and FSS-mediated endothelial cell function and has important implications in the pathogenesis of CS-induced pulmonary and cardiovascular diseases associated with endothelial dysfunction. Antioxid. Redox Signal. 12, 1355–1369.